Hydrochemistry Of Groundwater Pollution In The Urban Area Of Khan Younis City, Gaza Strip, Palestine - Abujaball, Mohammad S. M. (2017)
Groundwater is the only water source for drinking and domestic purposes in Khan Younis city and rainfall is the only source for fresh water recharge. Meanwhile, urbanization increment in last decades leads to groundwater overexploitation and quality highly polluted. The aim of this research is to explore the groundwater hydrochemical characteristics and mechanisms and hydrochemical processes controls the pollutants in the aquifer, determine mineral saturation states, explore the significance of deuterium versus oxygen18 of the groundwater system and determine the alterations according to groundwater flow direction. For this purpose, 240 groundwater samples from 20 wells were monitored and analyzed for major ionic parameters. While 35 samples analyzed for the isotopes. The result show that, the groundwater is near neutral to weakly alkaline in nature, have electrical conductivity, total dissolved solids, sodium, chlorides and nitrates values more than the maximum acceptable limits for drinking and domestic uses. Meanwhile, the correlation matrix indicates that, the groundwater is originated from a combination of many origins such as natural, mineral dissolution, saline water intrusion and anthropogenic pollution. While the most dominance hydrochemical facie for the water is sodium–chloride–sulfate water type. This water type is hard in nature, has ‘Low to Medium’ water class, unsuitable for drinking and domestic purposes. Calcite, dolomite, gypsum, fluorapatite and fluorite dissolutions and evaporation with ionexchange process are the mechanisms controlling the hydrochemical composition and pollutants enrichment in the groundwater. The isotopic values indicate that isotopes originated from groundwater mixing with rainfall and other water sources, the groundwater recharged from rainfall source and other sources and the area is characterized by semiarid climate. WATEQ4F model simulation shows that calcite and dolomite are in oversaturation states, gypsum and flourite are in undersaturation states and the aquifer is an open system to atmosphere. According to flow direction from east to west there are high impact of saline water intrusion in the east, calcite with dolomite abundance and dissolution in the middle, fluoridebearing minerals abundance and dissolution the east, sewage from cesspits on nitrate and phosphate contamination in the west and finally anthropogenic activities on boron and sulfate contamination in the east. There are minor decreases of in isotopic values from the east to west, indicating aquifer homogeneity.